Comparison of various wet-running multi-plate clutches with paper friction lining with regard to spontaneous damage behavior - Schneider, T.; Bedrikow, A. B.; Völkel, K.; Pflaum, H.; Stahl, K. (Tribology in Industry, 2021)
Wet-running multi-plate clutches fulfill a major safety-relevant role in drive trains and, as a result, damage to and failure of the clutch system must be strictly avoided, especially spontaneous damage. This paper deals with spontaneous damage to wet-running multi-plate clutches with paper friction lining with respect to spontaneous damage behavior. The paper presents a comparison method, by means of which the load-carrying capacity of various multi-plate clutches can be compared with regard to spontaneous damage based on experimental data and recommendations can be formulated. The experiments were performed on six different clutch variants, and the results were examined for significant differences. Various statistical tools were used to detect statistically significant variations. The experiments showed that higher load levels have a greater dispersion of the measured values, thus making comparisons more difficult. In the clutch variants investigated, significant changes in spontaneous damage behavior could only be detected when the cooling plate thickness or the carbon content was changed.
CRIS-Team Scopus Importer:2025-05-19
Keywords: Hot spots; Multiple plate clutch; Paper friction lining; Spontaneous damage; Wet friction clutch